4‐Hydroxybenzoic acid restores CoQ10 biosynthesis in human COQ2 deficiency. Issue 12 (17th October 2017) - Herebian, Diran; Seibt, Annette; Smits, Sander H. J.; Rodenburg, Richard J.; Mayatepek, Ertan; Distelmaier, Felix
Abstract: The clinical phenotypes of human CoQ10 ‐deficiency caused by COQ2 mutations range from fatal neonatal disease to adult‐onset multisystem atrophy. So far, treatment options for these diseases are unsatisfactory. Here, we demonstrate that supplementation of 4‐hydroxybenzoic acid (4‐HBA) fully restores endogenous CoQ10 ‐biosynthesis in COQ2‐deficient cell lines. This was accompanied by increased protein expression of CoQ10 ‐biosynthesis‐enzymes as well as a rescue of cell viability during stress conditions. In silico analysis suggested a ligand transportation path for 4‐HBA through the COQ2 protein towards the mitochondrial matrix side. This process is apparently hindered by disease‐causing mutations, which can be overcome by increasing 4‐HBA concentrations.